(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2018)
The tensoresistance at the uniaxial pressure along the crystallographic direction [100] for n-Si single crystals, which were irradiated by the different doses of gamma quants was investigated. On the basis of the theory of anisotropic scattering and experimental data of the tensoresistance the dependences of the parameter of mobility anisotropy on the uniaxial pressure for the data of single crystals are obtained. It has been shown that for unirradiated n-Si single crystals, the parameter of mobility anisotropy does not depend on uniaxial pressure since the alloying impurities of phosphorus will be completely ionized at T=77 K. For the gamma - irradiated n-Si single crystals the parameter of mobility anisotropy will decrease with an increase in exposure dose by reducing the screening effect. In this case, it is necessary to take into account the mechanisms of electron scattering on the impurity ions, impurity complexes, which consist of several ions of the impurity and on the fluctuation potential, which leads to the appearance of gradients of resistivity. The changing of relative contribution of these the scattering mechanismsat at the uniaxial pressure determines the obtained dependences of the parameter of mobility anisotropy and the tensoelectric properties of gamma-irradiated n-Si single crystals.